2018
DOI: 10.3390/ijms19061686
|View full text |Cite
|
Sign up to set email alerts
|

A WD40 Repeat Protein from Camellia sinensis Regulates Anthocyanin and Proanthocyanidin Accumulation through the Formation of MYB–bHLH–WD40 Ternary Complexes

Abstract: Flavan-3-ols and oligomeric proanthocyanidins (PAs) are the main nutritional polyphenols in green tea (Camellia sinensis), which provide numerous benefits to human health. To date, the regulatory mechanism of flavan-3-ol biosynthesis in green tea remains open to study. Herein, we report the characterization of a C. sinensis tryptophan-aspartic acid repeat protein (CsWD40) that interacts with myeloblastosis (MYB) and basic helix-loop-helix (bHLH) transcription factors (TFs) to regulate the biosynthesis of flava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 46 publications
3
53
0
Order By: Relevance
“…Taken together, both structural and regulatory genes in the catechin, l-theanine, and caffeine biosynthesis pathways were regulated by more than one TF family. Up to now, only a few TFs belonging to the MYB, bHLH, WD40, and WRKY families have been characterized functionally in tea [72][73][74][75]. Hence, based on our findings, it is hypothesized that those identified TFs are not only responsive to nutrient starvation but also may act as regulators of three major metabolites in tea.…”
Section: Differential Expressed Transcription Factors May Regulate Mementioning
confidence: 59%
“…Taken together, both structural and regulatory genes in the catechin, l-theanine, and caffeine biosynthesis pathways were regulated by more than one TF family. Up to now, only a few TFs belonging to the MYB, bHLH, WD40, and WRKY families have been characterized functionally in tea [72][73][74][75]. Hence, based on our findings, it is hypothesized that those identified TFs are not only responsive to nutrient starvation but also may act as regulators of three major metabolites in tea.…”
Section: Differential Expressed Transcription Factors May Regulate Mementioning
confidence: 59%
“…To date, certain MBW component genes that regulate flavonoid biosynthesis have been identified in tea plants. For instance, Sun, et al [57] showed that R2R3-MYB CsAN1 could interact with bHLH TFs (CsGL3 and CsEGL3) and CsTTG1 (a WD-repeat protein) to form an MBW complex to regulate anthocyanin accumulation; Liu, et al [58] found that CsWD40 (homologous to AtTTG1 TF) partners with bHLH (CsGL3 and CsTT8) and MYB (CsAN2 and CsMYB5e) TFs to form WBM complexes to control anthocyanin and proanthocyanidin biosynthesis; finally, the overexpression of certain tea plant MYB genes, such as CsMYB5a, CsMYB5b, CsMYB5e, CsMYB5-1, and CsMYB5-2, could alter anthocyanin and proanthocyanidin accumulation in other plants [59][60][61]. We found that most of the DEGs that were involved in the MYB, NAC, and WRKY classes were significantly upregulated in trichomes since tea trichomes usually exhibit glossy characteristics and might not have the capability to synthesize and store flavonoids and phenylpropanoids, especially anthocyanins and proanthocyanidins (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The WBM complexes not only regulate flavonoid synthesis, but also modulate trichome development through different TFs competing to form WBM complexes [6,16,62]. Recently, Liu, et al [58] indicated that the tea plant CsWD40 interacted with bHLH and MYB TFs to form WBM complexes that could alter anthocyanin accumulation and regulate trichome development. Nonetheless, known key TFs, such as GL1, GL3, EGL3, and TTG1, which were involved in trichome development, were not determined to be expressed at a significant level, although TFs, such as TTG1 (TEA000080), were upregulated in trichomes.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas C1 and MYB110 were downregulated by UV-B. C1 repressed DFR and UFGT expression levels [73], while MYB110 appeared to be the activator of anthocyanin biosynthesis in purple kiwifruit [74]. Therefore, the transcription factors mentioned above may be the key TFs to regulate anthocyanin synthesis induced by ultraviolet light in tea plant 'Ziyan'.…”
Section: Activity Of Enzyme and Degs Involved In Anthocyanin Biosynthmentioning
confidence: 98%